Legal Protection of the Parties in the Transfer of Rights in the PPAT Sale and Purchase Deed (AJB) Against the Cancellation of Land Ownership Certificates in the Medan High Court Decision Number 280/PDT/2020/PT MDN - Reni Suryani; Sufiarina; Safrida; Eliana (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purposes of this research are: To find out the legal protection of the buyer of land ownership rights after the cancellation of the certificate by the Medan High Court and to find out the responsibility of the National Land Agency for issuing certificates on the basis of the PPAT sale and purchase deed after the Medan High Court Decision Number 280/Pdt/2020/PT MDN . The research method used is normative juridical research with a statutory approach, then a concept approach and a case approach. The results of this study note that the legal protection for the buyer of land ownership rights after the cancellation of the certificate by the Medan High Court, that the issuance of a certificate on the basis of a deed of sale and purchase by a PPAT who is not authorized and exceeds the term of office is taken through a judicial process, if the deliberation process for consensus is carried out in outside the court using BPN as a mediator did not find an answer. As a general official, the PPAT has a code of ethics and knowledge regarding the authority to make the deeds. 2. BPN's responsibility for the issuance of certificates on the basis of the PPAT sale and purchase deed after the Medan High Court Decision Number 280/Pdt/2020/PT MDN, the issuance of certificates with deed of transfer of rights by an unauthorized PPAT regarding PP No. 24 of 1997 concerning Land Registration in the form of cancellation of certificates which were later issued by BPN, and as a vertical institution BPN is responsible for issuing certificates because those assigned the task of carrying out land registration activities